Business Communication - AD2251 - 202201 - Ontaneda Oleas, Elizabeth Diana (2022)
Course Overview: This course teaches effective communication practices necessary in professional business settings. Course instruction focuses on written, oral, and interpersonal communication strategies essential for success in business environments. In addition, as a fully online class, this course teaches online collaboration skills and use of various online collaborative tools. Prerequisite Requirements: No prior business communication knowledge is assumed in this course. As such, there are no prerequisite requirements for BCOM 314R (UPC: AD2251).